Apoptosis Sel Otot Rangka dan Perubahan Berat Badan pada Tikus Diabetes yang Diberi Ekstrak Umbi Bawang Dayak (Eleutherine palmifolia L., Merr) - Lailia Dwi Kusuma Wardhani; Olan Rahayu Puji Astuti (Universitas Wijaya Kusuma Surabaya, 2020)
This study was undertaken to investigate the antidiabetic and antioxidant of bawang dayak bulbs (Eleutherine palmifolia L., Merr) extract (BDBE) on skeletal muscle cell apoptosis and body weight change in diabetic rat. Single doses alloxan 120 mg/kgBW were administered intraperitoneally to get diabetic rat. Twenty four male Wistar rat of three months old were used in this study. Rat were devided into six groups: negative control group (were not diabetic and treated) (K0), positive control group (were diabetic and treated CMC-Na) (K1), drug control group (were diabetic and administrated metformin as a standard drug) (K2), BDBE dosed 200 (P1), 400 (P2), and 800 mg/kgBW (P3). The treatment was conducted for 14 days. Hypoglycemic effect and body weight measured of all mice was determined at day 7 and 14 of treatment. At the end of research, all of rat were sacrificed and m. gastrocnemius were collected for apoptosis analysis by TUNEL staining and atrophy analysis by Hematoxilin-Eosin staining. The result of this study showed that BDBE decreased skeletal muscle cell apoptosis and mantained the skeletal muscle fiber diameter (atrophy) and body weight change in diabetes rat.